The design of a low cost ad-hoc network for short distance data acquisition - Rossouw, Cornelius Marais (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--Stellenbosch University, 2008.